Evaluation of natural culture media for the maintenance of Colletotrichum sp., and Saccharomyces cerevisiae - Romero Barranco, Clara; Aguirre Pérez, Laura; Plata Alfaro, Nestor; Yepes Escorcia, Jayr (Scientia et Technica, 2018)
In this paper the productivity, selectivity and effect of the pH of natural culture media for the maintenance of Colletotrichum sp., and Saccharomyces cerevisiae were evaluated. The productivity and selectivity were determined by the ecometric method and by measuring the radial growth, the pH effect by spectrophotometry and mycelial growth. The media were not selective and were highly productive for yeast recovery, with best results at 5% concentration in all cases, while for mold the best result was at 10 and 20% concentrations, pH levels did not cause marked alterations in the growth of Colletotrichum sp., And the evaluated yeast. The natural culture media evaluated were not selective, but allowed adequate growth and development for Colletotrichum sp., and Saccharomyces cerevisiae indicating that their nutritional contribution is comparable to that of commercial growing media.